REKONSTRUKSI KONSEP SIKLUS KEHIDUPAN MANUSIA DALAM PERSPEKTIF TEOLOGI PENDIDIKAN ISLAM - Akbar, Ghufran; Arwani, Muhammad; Syahid, Ahmad; Basri, Hasan; Sadiah, Dewi (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2025)
This study is motivated by the limitations of contemporary human development theories, which predominantly emphasize biological and psychological dimensions while overlooking the spiritual and eschatological aspects essential to the Islamic theological perspective. This gap necessitates a more comprehensive reconstruction rooted in Islamic normative sources and aligned with the needs of modern education. This study aims to reconstruct the concept of the human life cycle from the perspective of Islamic educational theology, identify the stages of life that are relevant to the framework of Islamic education, and explain their implications for Islamic educational practice. Employing a descriptive qualitative method, the research integrates content analysis and thematic analysis of primary sources—Qur’an, Hadith, and classical texts—alongside contemporary academic literature. The findings reveal that the Islamic perspective on the human life cycle comprises six interconnected phases: pre-birth, childhood, adolescence, adulthood, old age, and post-death, all of which relate closely to fitrah, spiritual purification (tazkiyah), cultivation of adab, and eschatological orientation. The study proposes a holistic–transcendental conceptual model grounded in tawhid that strengthens the epistemology of Islamic education and offers a theoretical alternative for the advancement of Islamic educational practice in the modern era.